Sistem Informasi Wedding Decoration Berbasis Web Mobile Pada Melati Wedding Organizer Kota Lubklinggau - Muhammad Nur Alamsyah; Hardi Mulyono; Deka Purnama Sari (Journal of Informatics Management and Information Technology, 2021)
Wedding Decoration is a service that provides a special service in decorating the wedding venue as well as the preparation of the bride and groom and their families by carrying out a series of wedding events according to a predetermined schedule and budget. The design of the Wedding Decoration information system is made by utilizing Mibile Web-based technology, this aims to expand the area of ??marketing promotions for wedding packages and simplify the ordering process. Wedding Decoration Information System, built with PHP programming language with MySQL as the database. The design (application programming interface abbreviated as API) is built based on the Mobile Web, which is a web display that can adapt to the current Android smartphone screen. It can be concluded that the application that has been built can provide information and provide an online Wedding Decoration ordering process and provide special access to people who want to place an order for a Wedding Decoration to be able to directly choose a Wedding Decoration design.